BMW Ginger Processing Plant - Ordoñez, Lourdes L. (College of Engineering, 1981)
Plant name: BMW Ginger Processing Plant -- Plant location: Anabu, Imus, Cavite -- Product name: GINGERLITE -- Capacity: 3000 tons per year -- Fixed capital investment: P 4,092,556.10 -- Operating cost: P 8,390,325.70 -- Sales: P 9,963,590.90 -- Payout time: 2.06 years -- Break-even point: 43% capacity -- Shutdown point: 24% capacity